THE INFLUENCE OF LEADERSHIP STYLE, WORK MOTIVATION ON EMPLOYEE PERFORMANCE MEDIATED BY JOB SATISFACTION IN EMPLOYEES AT BHAKTI HUSADA BEKASI - Yoga Pratama; Retno Purwani Setyaningrum (Asosiasi Dosen Muda Indonesia, 2026)
Human resource management is a process that involves the utilization of individuals or staff, including the recruitment, use, development, and maintenance of existing human resources to support an organization or its activities. The existence of quality human resources in a company can improve effective and directed employee performance in achieving predetermined targets. Employee performance is the result of a person's activities that reflect the quality and quantity of work performed. This study aims to understand the influence of leadership style and work motivation on employee performance with job satisfaction as a mediating variable at Bhakti Husada Hospital, Bekasi. The method used in this study is quantitative, with a sample of 67 respondents from a total population of 203 employees at Bhakti Husada Hospital, Bekasi. Data analysis was carried out using SmartPLS 3.0 software, and data collection was carried out through Google Forms. The results of the study indicate that leadership style has a significant influence on employee performance. On the other hand, work motivation does not show a significant influence on employee performance.